2000
DOI: 10.1200/jco.2000.18.21.3699
|View full text |Cite
|
Sign up to set email alerts
|

Time to Clinical Response: An Outcome of Antibiotic Therapy of Febrile Neutropenia With Implications for Quality and Cost of Care

Abstract: Despite virtually identical rates of response, time to clinical response and estimated cost of care varied significantly among regimens. An early discharge strategy based on our definition of the time point of clinical response may further reduce the cost of treating non-low-risk patients with febrile neutropenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
5

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 25 publications
1
27
0
5
Order By: Relevance
“…In an analysis of 488 episodes of febrile neutropenia, Elting et al 79 found that the median time to clinical response in hospitalized patients with cancer was 5-7 days. In contrast, in low-risk patients, it has been shown that the median time to defervescence is as short as 2 days.…”
Section: Timing Of Evaluation Of the Response To The Initial Empiricamentioning
confidence: 98%
“…In an analysis of 488 episodes of febrile neutropenia, Elting et al 79 found that the median time to clinical response in hospitalized patients with cancer was 5-7 days. In contrast, in low-risk patients, it has been shown that the median time to defervescence is as short as 2 days.…”
Section: Timing Of Evaluation Of the Response To The Initial Empiricamentioning
confidence: 98%
“…Despite improvements in environmental controls, antibiotic prophylaxis and therapy, it remains a significant clinical problem [2,3]. The mortality from FN may be up to 10%, depending on the population studied, and FN still accounts for the majority of chemotherapy-associated deaths [1,4,5]. Extensive investigations do not usually yield a causative organism and treatment remains empirical based on known patterns of infection [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Hence it is recommended that the initial antibiotic regimen could be continued for 5 days, despite fever spikes, unless a change is needed either due to clinical deterioration of patient or culture reports indicating otherwise. A study involving 488 febrile neutropenic patients has revealed that median time for clinical response was 5 (2-7) days 19 .…”
Section: Antibiotic Therapy During the First Weekmentioning
confidence: 99%